Interferences between time and space in advanced age. - Jagorska, Cindy; Steinecker, Isa; Riemer, Martin (Memory & Cognition, 2026)
Perceptual interference between time and space has been reported in neonates, infants, children, and young adults, but to date it is unknown how space–time interference develops in advanced age. The presented study aims to bridge this gap by testing these interference effects in older (60 + years) and younger (18–35 years) participants. We asked our participants to reproduce the temporal duration or the spatial size of realistic three-dimensional (3D) stimuli (virtual rooms of different size presented in immersive virtual reality (VR)) and of abstract two-dimensional (2D) stimuli (squares presented on a PC screen). The results show that space judgments of older versus younger adults are more affected by irrelevant temporal information (time-on-space effect), whereas the reverse space-on-time effect was not significantly different between age groups. Space–time interference did not differ between 3D and 2D task versions. Together, our findings provide first insights into the development of space–time interference in advanced age.